Fish biomass data during Alkor cruise AL608 - Luisa Listmann (PANGAEA, 2025)
This data set includes fish biomass data collected during the RV ALKOR cruise AL608 conducted in March 2024 in the Western Baltic Sea by the University of Hamburg. The cruise was part of the 5-year MARSYS teaching cruise program of the University of Hamburg GFP20-1_047. Fish biomass was taken after sorting through a complete fish haul into the single species and weighing them on a scale on board.